Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21608/ejpa.2020.117838
|View full text |Cite
|
Sign up to set email alerts
|

A study of health-related quality of life in pediatric atopic dermatitis

Abstract: A study of health-related quality of life in pediatric atopic dermatitis Original article Background: Children of atopic dermatitis (AD) have difficulties in social adaptation and academic achievements. Health related quality of life (HRQOL) is a multidimensional measure not restricted to physical effects of disease or its treatment. Objective: We sought to assess, through validated questionnaire sets, the impact of AD on the HRQOL of children and their parents or caregivers. Methods: This analytical cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Another study by Hossny et al found that of 85 children with AD from the children's hospital in Ain Shams University in Egypt, more than half of the children (55.4%) had severely affected QoL, with itching and pain being a primary concern. A statistically significant effect of face eczema on QoL of children was also reported [35,36]. In this study, 84.6% of the children believed that the disease had a great impact on their relationship with friends and play, while this was reported in only 2% by other investigators, highlighting the social stigma that patients may feel.…”
Section: Qol Impactsupporting
confidence: 54%
See 2 more Smart Citations
“…Another study by Hossny et al found that of 85 children with AD from the children's hospital in Ain Shams University in Egypt, more than half of the children (55.4%) had severely affected QoL, with itching and pain being a primary concern. A statistically significant effect of face eczema on QoL of children was also reported [35,36]. In this study, 84.6% of the children believed that the disease had a great impact on their relationship with friends and play, while this was reported in only 2% by other investigators, highlighting the social stigma that patients may feel.…”
Section: Qol Impactsupporting
confidence: 54%
“…It is burdensome to care for a child with AD because of the special needs of the patient, such as with bathing, wet dressings, topical application, and household-related tasks and responsibilities such as food restrictions, clothing selection, laundry, and house cleaning to avoid potential allergens [36]. This is in addition to the added costs of implementing these lifestyle adjustments [1].…”
Section: Qol Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease tends to manifest more in dry weather [ 9 , 10 ]; therefore, the burden may vary according to the climate of each country. The burden of AD in the Middle East and Africa has been discussed in a recent literature review [ 11 ], and other reviews have estimated its prevalence or burden in specific cities [ 12 , 13 ]; however, to our knowledge, this is the first study to quantify the burden of the disease in adults and adolescents in specific countries in the region. Country-specific burden data are essential to allow decision-makers to make evidence-based decisions and efficiently allocate the available resources.…”
Section: Introductionmentioning
confidence: 99%